Small dense low-density lipoprotein as biomarker in the elderly - Katajamäki, Taina T.; Koivula, Marja-Kaisa; Salminen, Marika J.; Vahlberg, Tero; Heikkilä; Elisa; T.M.; Viljanen, Anna M.; Löppönen, Minna K.; Isoaho, Raimo E.; Kivelä, Sirkka-Liisa; Viitanen, Matti; et al. (Elsevier BV, 2025)
Objectives: Small dense low-density lipoprotein (sdLDL) is atherogenic and associated with atherosclerotic cardiovascular diseases (ASCVD). The aim of this study was to perform the prospective evaluation of sdLDL-c in new ASCVD over 18 years of follow up, and to compare the association of sdLDL-c and conventional lipids and apolipoproteins with ASCVD in the elderly.
Methods: This prospective study included a total of 1770 subjects ≥ 64 years of age with an 18-year follow-up period. The determination of sdLDL-c was measured by a homogenous, selective enzymatic method. Levels of total cholesterol (TC), high-density lipoprotein cholesterol (HDL-c) and triglycerides (TG) were determined by enzymatic methods. Apolipoproteins, ApoA1 and ApoB, were analyzed by immunonephelometric methods. Low-density lipoprotein cholesterol (LDL-c) levels were calculated using the Friedewald formula.
Results: According to Pearson's correlation coefficients, sdLDL-c concentration was positively correlated with LDL-c, nonHDL-c, TC and ApoB concentrations. During follow up, sdLDL-c was significantly associated with new ASCVD in men aged 64-76 years in both unadjusted and adjusted Cox regression models. The adjusted hazard ratio (95 % CI) for sdLDL-c was 1.61 (1.13-2.28). No significant associations between sdLDL-c and ASCVD were observed in men aged 77-97 years, nor in women aged 64-79 or 80-100 years.
Conclusions: Lipid and apolipoprotein concentrations of the elderly were high compared to the recommended target values. In addition, lipid and apolipoprotein baseline concentrations were not higher in the ASCVD group than in the control group. Our results indicated that sdLDL-c is as good a marker as ApoB and better than LDL-c.